Obstacles to effective strategy implementation: Insights from Agricultural Cooperatives in Malawi - Thokozani Zylma Madumuse; Mubanga Mpundu (Advanced Research in Economics and Business Strategy Journal, 2025)
The strategy implementation literature remains fragmented, thus requiring further empirical studies to explain SI challenges in different types of organizations. This has influenced the nature of this study, which aims to identify barriers in SI in the novel organizational context of agriculture cooperatives.